2014
DOI: 10.1016/j.expthermflusci.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic instabilities in micro-scale flows

Abstract: Many artificial and natural fluids contain macromolecules, particles or droplets that impart complex flow behaviour to the fluid. This complex behaviour results in a non-linear relationship between stress and deformation standing in between Newton's law of viscosity for an ideal viscous liquid and Hooke's law for an ideal elastic material. Such non-linear viscoelastic behaviour breaks down flow reversibility under creeping flow conditions, as encountered at the micro-scale, and can lead to flow instabilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Similarly, in the inertia‐free case of polymer solutions at Re ≪ 1, a flow instability analogous to turbulence arises because nonlinearities in the constitutive relation between stress and deformation (Section ) destabilize the steady‐state laminar solution. Such instabilities were theorized as early as the 1970s and have been catalogued in diverse geometries, including concentric cylinders, rotating disks, and curved channels since the late 1980s . In all cases, an instability is observed for strong enough flow in geometries with a large amount of streamline curvature.…”
Section: Unstable Flow Of Polymer Solutionsmentioning
confidence: 99%
“…Similarly, in the inertia‐free case of polymer solutions at Re ≪ 1, a flow instability analogous to turbulence arises because nonlinearities in the constitutive relation between stress and deformation (Section ) destabilize the steady‐state laminar solution. Such instabilities were theorized as early as the 1970s and have been catalogued in diverse geometries, including concentric cylinders, rotating disks, and curved channels since the late 1980s . In all cases, an instability is observed for strong enough flow in geometries with a large amount of streamline curvature.…”
Section: Unstable Flow Of Polymer Solutionsmentioning
confidence: 99%
“…As it was mentioned previously, at the micro-scales (typical scales from the human circulatory system), the elastic effects are enhanced even at low Reynolds numbers [7,54,55]. The complex rheological behaviour of whole blood has been studied and continues to be investigated using new technological advances [56,57].…”
Section: Complex Fluids In the Human Body For Blood Flowmentioning
confidence: 96%
“…In the shear-layer transition regime, the increase of the wake angle and pressure rise coefficient reduced the drag coefficient and narrowed the near wake. At the micro scale, the relevance of fluid elasticity is enhanced and elastic instabilities can be observed easily even at low or negligible Re [7,67]. Campo-Deaño et al [54] showed that, for a viscoelastic fluid (Boger fluid), symmetric vortices started to form upstream of a hyperbolic contraction at a critical Re of 0.82; meanwhile, for the same micro channel and flow conditions, for a Newtonian fluid, the critical Re at which symmetric vortices start to form downstream of the hyperbolic contraction is higher (Re = 49.3) due to inertial effects ( Figure 2).…”
Section: Complex Fluid Nature Viscosity and Elasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the channel with periodical cross sections, such as the channel with side wells or with expansion/contraction cavity arrays, the hoop stress or the secondary flow force was induced for the particle focusing in different media . Significant secondary flow was generated in these microchannels because of suddenly changed cross section and viscoelastic instabilities in micro‐scale flow , which would induce high pressure drop and disturb focused particle stream . Although numerous studies have been done on the viscoelastic particle focusing, the length of existing microchannels is typically long because of the weak elastic effect at low flow rates (most were longer than 4 cm), making it unsuitable to be integrated in small chip area.…”
Section: Introductionmentioning
confidence: 99%